Natural resource management and poverty reduction - Christopher John Heady (Fondazione Eni Enrico Mattei (FEEM), 1998)
This paper considers the relationship between natural resource management and poverty by analysing a specific example: an inland fishery in Bangladesh. The analysis involves substantial extensions to standard models and allows the simulation of market distortions and alternative management policies, using data from the fishery. The simulations show that fish migration is the most important distortion. They also show that both wage reductions and bans on capital-intensive gears can increase employment, and so reduce poverty, without endangering the sustainability of the resource. The techniques used here can be applied to other fisheries and non-fish natural resources.
Keywords: O2; Q2; 330; Renewable resources; Poverty reduction; Fishery models; Environment and development; Fischereiressourcen; Rohstoffpolitik; Umweltpolitik; Armutspolitik; Theorie; Bangladesch